Bladder colloid carcinoma: A case report - Mahdi Marrak; Kays Chaker; Yassine Ouanes; Alia Zehani; Mohamed Trigui; Yassine Nouira (Urology Case Reports, 2023)
Non-urothelial bladder cancers are rare. We report the case of a 72-year-old who consulted for terminal hematuria evolving for three months. Computed Tomography scan showed a tumor of the anterior wall of the bladder. The patient underwent a transurethral resection of the bladder tumor. The histological examination of the tumor showed a bladder colloid carcinoma. The extension evaluation showed pulmonary and bone metastases. The patient received chemotherapy.